Mitigation of Methanogenesis in Ruminants Using Wheatgrass Compounds as Methyl Coenzyme M Reductase Inhibitors: An In Silico Study - Ananya Saluguti; Ameer Khusro; Prabhalakshmi Balasubramaniyan; Dhanraj Ganapathy; Maximilian Lackner; Moises Cipriano-Salazar (BioResources)
Ruminants are significant contributors to methane (CH4) emissions due to methanogenesis by their gut microbiomes. The enzyme methyl coenzyme M reductase (MCR) is crucial for this process in rumen archaea. Targeting MCR via computational tools has emerged as a novel approach to reduce CH4 emissions in ruminants by inhibiting methanogenesis. This study focused on evaluating wheatgrass (Thinopyrum intermedium) compounds as potential MCR inhibitors using in silico methods. Initially, 21 wheatgrass compounds were selected, and their drug-likeness traits were assessed using Lipinski’s rule of five. Five compounds, namely 2,4,6-trimethyl-1,3-phenylenediamine, Caryophyllene oxide, Caryophyllene, N,N-tetramethylene-.alpha.-(aminomethylene) glutaconic anhydride, and n-hexadecanoic acid met all criteria. These compounds were further analysed for absorption, distribution, metabolism, and excretion (ADME) properties using the Swiss ADME tool, confirming their drug-likeness traits with no Lipinski’s violation. Molecular docking analysis was performed using the CB-Dock2 tool to assess binding interactions with MCR. The compounds showed binding affinities in the following order: N,N-tetramethylene-.alpha.-(aminomethylene) glutaconic anhydride (-7.3 kcal/mol) > Caryophyllene (-6.8 kcal/mol) > Caryophyllene oxide (-6.7 kcal/mol) > n-hexadecanoic acid (-6.3 kcal/mol) > 2,4,6-trimethyl-1,3-phenylenediamine (-6.0 kcal/mol). These findings suggest that the selected wheatgrass compounds have potential as anti-methanogenic agents, positioning them as promising MCR inhibitors for mitigating CH4 emissions in ruminants.